THE CLUSTER INTERACTIVE METHOD: A PARADIGM FOR ENHANCING LEARNING IN COMPUTER SCIENCE CLASSES - Yuldashev Abdurauf Rozmatjonovich (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific article aims to introduce the Cluster Interactive Method (CIM), a teaching approach designed to enhance learning outcomes in computer science classes. The CIM encompasses a series of interconnected stages that incorporate collaborative activities, problem-solving exercises, and hands-on experiences. By promoting active student engagement, the CIM aims to a) deepen conceptual understanding, b) cultivate critical thinking skills, c) foster teamwork and communication, and d) improve overall performance in computer science education. In this article, we explore the different stages of the CIM and discuss its potential impact on computer science education.